Meningkatkan Motivasi Belajar Melalui Model Pembelajaran Problem Based Learning (PBL) dengan Media Canva Bagi Siswa Fase F SMA Negeri 1 Prambanan Tahun Pelajaran 2024/2025 - Christina Heti Tyas Widayanti; Anselmus Yata Mones; Maria Margaretha Dwilinda (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to determine whether the use of the PBL learning model with Canva media can increase student learning motivation, which is indicated by increased interest, active participation, and enthusiasm of students in participating in learning activities through the PBL model in students at SMA Negeri 1 Prambanan. This type of research is classroom action research with research steps, namely planning, implementation, observation, and reflection in each cycle. This study consists of two cycles. The research location is at SMA Negeri 1 Prambanan Sleman in Phase F students. Data collection techniques are observation, questionnaires and interviews. The results of the study in cycle 1 can be concluded that student motivation gets the criteria